Stereoconvergent 1, 4‐Addition Reaction of 5H‐Oxazol‐4‐ones with E, Z Isomeric Mixture of Alkylidene β‐Ketoesters Catalyzed by Chiral Guanidines. Issue 39 (8th June 2018) - Misaki, Tomonori; Tatsumi, Toshifumi; Okamoto, Tatsumasa; Hayashi, Yusuke; Jin, Nari; Sugimura, Takashi
Abstract: A 1, 4‐addition reaction of 5 H ‐oxazol‐4‐ones to alkylidene β‐ketoesters, which was catalyzed by using chiral guanidines via a dynamic kinetic resolution process that involved geometric isomerization of the alkylidene β‐ketoesters, was developed. This method allowed using E, Z isomeric mixture of various acyclic alkylidene β‐ketoesters to obtain the products stereoselectively. The relation between the geometry and the stereoselectivity of products was investigated, and the derivatization of the products to the corresponding α‐acyl‐γ‐lactone was performed. Abstract : A chiral guanidine‐catalyzed 1, 4‐addition reaction of 5 H ‐oxazol‐4‐ones2 to nearly one equivalent of a geometric mixture of alkylidene β‐ketoesters3 via a dynamic kinetic resolution process that involved geometric isomerization of the alkylidene β‐ketoesters was developed. The relation between the geometry and the stereoselectivity of products was investigated, and the derivatization of the products to the corresponding α‐acyl‐γ‐lactone was performed (see scheme).